2013
DOI: 10.4149/bll_2013_076
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitides as a rare cause of intermittent claudication

Abstract: Intermittent claudication of the lower extremities is a common symptom described in older patients with atherosclerotic peripheral arterial disease. Peripheral arterial disease due to atherosclerosis is known to be associated with a higher risk of myocardial infarction, stroke and all-cause mortality. However, if intermittent claudication appears in a younger group of patients or older patients in absence of traditional risk factors for atherosclerosis such as smoking, dyslipidemia, arterial hypertension and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…There are few case reports of PAN presenting as PVD and limb vessel involvement. [1234] Similar to our case, the case reported by De Golovine et al . [1] had lower limb ischemia and bilateral femoral artery involvement.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There are few case reports of PAN presenting as PVD and limb vessel involvement. [1234] Similar to our case, the case reported by De Golovine et al . [1] had lower limb ischemia and bilateral femoral artery involvement.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, in a patient with premature PVD common causes such as family history of premature atherosclerosis, smoking, hyperlipidemia, diabetes mellitus, hypertension, and hypercoagulable states need to be categorically ruled before thinking of primary vasculitis as they are more common. [2] Héron et al . reported a 33-year-old hypertensive woman presenting with acute occlusion of the three infrapopliteal arteries of the right leg that led to the diagnosis of PAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCA is the most common of the vasculitides affecting the peripheral vasculature, which has been reported to be symptomatic in up to 16% of patients with temporal arteritis, with up to a further 16% at risk of rapidly progressing to critical limb ischemia resulting in amputations (29)(30)(31). Assie et al also demonstrated that GCA had a greater predilection for upper limb vasculature of up to 77.7% (31).…”
Section: Vasculitismentioning
confidence: 95%
“…Other rare diseases, including Cogan's syndrome and relapsing polychondritis, can cause vasculitis of large-or medium-sized vessels. Small-vessel vasculitides include cryoglobulinemic vasculitis, leukocytoclastic vasculitides such as Henoch-Schonlein purpura and isolated cutaneous leukocytoclastic vasculitis, and vasculitis secondary to systemic autoimmune disease, including rheumatoid arthritis, systemic lupus erythematosus (SLE), and scleroderma [30,47]. It is worth noting that there is the possibility of atypical lesion distribution for any type of vasculitides (Figures 10 and 11).…”
Section: Other Vasculitidesmentioning
confidence: 99%